Tauhidunomics: Religious Ethics and Economic Growth in Tasikmalaya - Mardani, Dede Aji; Masuroh, Imas Siti; Ali, Wan Zailan Kamarudin Wan (TEMALI : Jurnal Pembangunan Sosial, 2023)
This research aims to analyze the concept of Tauhidunomics used by Muslim entrepreneurs in Tasikmalaya. The method used is qualitative, with interview techniques from sources scattered in the city center and Tasikmalaya. The findings of this study indicate that Tauhidunomics is a concept of trading that Muslim entrepreneurs carry out by holding on to norms (the holy book-sunnah) and religious religiosity (the role of religious leaders and communities). The concepts and values of Tauhidunomics are individual honesty, hard work, frugality, commitment, openness, and calculation, and the social as diligent giving, providing guarantees and advancing fellow employees.